Young Americans 2 : New American Art at the Saatchi Gallery - Adams, Brooks; Liebmann, Lisa (London : The Saatchi Gallery, 1998)
Ashkin, Michael ; Bickerton, Ashley ; Currin, John ; Diamond, Jessica ; Dunham, Carroll ; Friedman, Tom ; Kcho ; Kersels, Martin ; Ketter, Clay ; LeDray, Charles ; Lowe, Robin ; Morris, Sarah ; Owens, Laura ; Peyton, Elizabeth ; Salle, David ; Stockholder, Jessica ; Tolle, Brian ; Winters, Terry ; Yuskavage, Lisa
biog., ind. tent. [8 p.]
Engels
Young Americans 2, The Saatchi Gallery, London, Part 1 : 04 - 07/1998, Part 2 : 09 - 11/1998
boek
Keywords: Amerika